The Delphi Method as a technique to study Validity of Content. - Gil, Beatriz; Pascual-Ezama, David (Anales de Psicología / Annals of Psychology, 2012)
Finding procedures that may guarantee high levels of validity is one of the big challenges in methods in psychology nowadays. In the present study, we show the Delphi method as a technique to study the validity of content. This method shows an important advantage regarding to traditional expert methods: it is flexible and dynamic in its application, allowing the presence of feedback between the expert participants. We applied the Delphi method during the development of a questionnaire of individual investors’ behavior in the stock exchange (Pascual-Ezama, et al., 2010), also calculating congruency indexes (Rovinelli y Hambleton, 1977) along the different stages of the Delphi application. The results show that the Delphi method may be a good tool in order to guarantee high levels of validity of content in a questionnaire. Advantages as well as disadvantages of the traditional expert methods and the Delphi method, and how the present study joins quantitative and qualitative methods like the Delphi, are discussed. This link between those different types of methods is, with no doubt, one of the fields to explore and develop in methodology nowadays.